The Analysis of Individual’s Behavioral Intention in Using Mobile Banking Based on TAM and UTAUT 2 - JIHAN ENGGAR SAFIRA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this research is to examine the factors that influence the behavioral intention of consumers to use mobile banking services. The proposed model has factors from the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT2). This research is a quantitative research and the data was collected using survey method, i.e. questionnaires. The respondents are 314 undergraduate active students from accounting department in Faculty of Economics and Business, Universitas Brawijaya. The research data and hypothesis are analyzed using structural equation modeling (SEM) based on partial least squares (PLS). The research findings mainly indicate that behavioral intention to use mobile banking is significantly and positively influenced by perceived usefulness, social influence and facilitating conditions. In contrast, perceived ease of use and price value do not affect user’s behavioral intention to use mobile banking. Keywords: Perceived Usefulness, Perceived Ease of Use, Social Influence, Facilitating Conditions, Price Value, Behavioral Intention to Use Mobile Banking